Role of Innovation in Achieving Technology and Business Competitiveness - Natarajan, R. (Journal of Engineering Education Transformations, 2006)
Innovation is increasingly being recognised as the key to technology and business competitiveness. This paper explores the anatomy of Innovation, and attempts to identify the key success factors promoting Innovation, as also barriers and impediments to Innovation.